The Role of Sufism in the Identity Construction, Mobilization and Political Activism of the Barelwi Movement in Pakistan - Philippon, Alix (PARTECIPAZIONE E CONFLITTO, 2014)
This article intends to analyze the forms of political activism of the Barelwi movement, one specific Sufism oriented religious movement rooted in the 19th century, which has gradually politicized through Pakistani history. It has played a widely ignored role in the politics of Pakistan, may it be in party politics, social movements, or through the islamization of society. There are today about forty Barelwi or-ganizations differently located on a scale of politicization, protest and radicalization. These “neo Sufi or-ders” have constructed a distinct Sufi identity and evolved different strategies to defend their version of Islam and fight for an Islamic State, an endeavor which they call the system of the Prophet (Nizam-e Mus-tafa). The organizational form they adopted is a mixture of a Sufi order, an activist association and for some, a political party. In the framework of the “War against terror”, mainly targeting their more reformist doctrinal challengers, the Barelwi presence in the public sphere has increased. The different groups of the movement have organized many conferences and demonstrations aiming both at denouncing the “talibanization” of Pakistan and at reasserting the role of Sufis in the promotion of an Islam of “peace, love and tolerance” in contemporary Pakistan. Paradoxically, this movement has also undergone a process of radicalization, thus blurring the lines between peaceful activism and violent direct action.